2014
DOI: 10.1002/ieam.1487
|View full text |Cite
|
Sign up to set email alerts
|

Focal species of birds in European crops for higher tier pesticide risk assessment

Abstract: Focal species have been defined by the European Food Safety Authority (EFSA) as real species that represent others in a crop resulting from their potential higher level of exposure to pesticides. As such they are the most appropriate species for refining estimates of exposure further, through, for example, radio tracking and dietary studies. Plant protection product manufacturers collectively commissioned many studies in Europe, according to the EFSA guidelines, to identify focal species in different crops tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…Despite high FO field and FO survey values, application of criteria by Dietzen et al () exclude as focal species larger omnivorous birds such as crows, rooks, and starlings frequently observed in flocks in winter, which look for all foraging opportunities provided by the farming cycle but have no preference for winter cereal fields (Whitehead et al ; Mason and MacDonald ). These species are frequently considered agricultural pests by farmers, leading to use of bird control methods to prevent crop damage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite high FO field and FO survey values, application of criteria by Dietzen et al () exclude as focal species larger omnivorous birds such as crows, rooks, and starlings frequently observed in flocks in winter, which look for all foraging opportunities provided by the farming cycle but have no preference for winter cereal fields (Whitehead et al ; Mason and MacDonald ). These species are frequently considered agricultural pests by farmers, leading to use of bird control methods to prevent crop damage.…”
Section: Discussionmentioning
confidence: 99%
“…Hence it can be important to establish relevant focal species in risk assessment, introducing greater realism for refined risk assessments, when needed. Various authors (e.g., Crocker and Irving ; CSL ; Andrade et al ; MNHN ; Dietzen et al ) have suggested lists of real focal bird species for European crop scenarios. However, few of these focus on the scenario of newly drilled treated cereal seeds, and none do so with specific reference to France.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of ERA, focal bird species have been defined by EFSA as bird species that represent others in a crop resulting in realistic worst case for ERA due to their potential higher level of exposure to pesticides (Dietzen et al, 2014). Because in the example provided by Dietzen et al (2014) focal taxa are selected according to exposure rather than recovery, it is, within the context of this scientific opinion, important to consider the traits of focal taxa likely to determine their recovery. Species which are the least able to recover following use of a potential stressor may possess multiple traits that predispose them to poor recovery.…”
mentioning
confidence: 99%